# Find p(0), p(1) a

(i) p(y) = y2 – y + 1

p (0) = (0)2 – (0) + 1 = 1

p (1) = (1)2 – (1) + 1 = 1

p (2) = (2)2 – (2) + 1 = 3

(ii) p(t) = 2 + t + 2t2 – t3

p (0) = 2 + 0 + 2 (0)2 – (0)3 = 2

p (1) = 2 + (1) + 2 (1)2 – (1)3

= 2 + 1 + 2 – 1 = 4

p (2) = 2 + 2 + 2 (2)2 – (2)3

= 2 + 2 + 8 – 8 = 4

(iii) p(x) = x3

p (0) = (0)3 = 0

p (1) = (1)3 = 1

p (2) = (2)3 = 8

(iv) p(x) = (x – 1) (x + 1)

p (0) = (0 – 1) (0 + 1) = (-1) (1) = -1

p (1) = (1 – 1) (1 + 1) = 0 (2) = 0

p (2) = (2 – 1) (2 + 1) = 1 (3) = 3

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses
RELATED QUESTIONS :

The zeroes of theRS Aggarwal & V Aggarwal - Mathematics

Zero of the polynRS Aggarwal & V Aggarwal - Mathematics

If 2 and -1/3 areRS Aggarwal & V Aggarwal - Mathematics

If (x + 1) is a fRS Aggarwal & V Aggarwal - Mathematics

If (x2RS Aggarwal & V Aggarwal - Mathematics

The zeroes of theRS Aggarwal & V Aggarwal - Mathematics

The zeroes of theRS Aggarwal & V Aggarwal - Mathematics

If p(x) = x3RS Aggarwal & V Aggarwal - Mathematics

If p(x) = (xRS Aggarwal & V Aggarwal - Mathematics

The coefficient oRS Aggarwal & V Aggarwal - Mathematics